Pola Interaksi Pendidikan Dalam Proses Pembelajaran Agama Islam - Supriyadi Supriyadi (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Association of Muslim Community in ASEAN (AMCA), 2016)
Interaction patterns of education is interwoven communication between religious teachers with students in the classroom using the conventional pattern of education approach in the process of learning Islam in a primary school, so the impact on the teachers who teach well being. This is based on this paper in an effort to analyze the interaction patterns of education that occurs in the process of learning the Islamic religious education which take place in class and gain knowledge about the value of what the dominant value shape the education interaction in the process of learning the Islamic religion in the classroom.